2010
DOI: 10.1021/om9011054
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of [Fe2(CO)6(μ-S2)] toward a Base-Containing Diphosphine (Ph2PCH2)2NCH3: Formation of Diiron Carbonyl Compounds Having Polydentate Heterofunctionalized Phosphine (PNS = Ph2PCH2N(CH3)CH2S) and Bidentate Thiophosphinito (Ph2PS = PS) Bridges

Abstract: Reaction of the base-containing diphosphine (Ph 2 PCH 2 ) 2 NCH 3 with [Fe 2 (CO) 6 (μ-S 2 )] (1) yielded at room temperature the novel compound [Fe 2 (CO) 4 (μ-κ 1 :κ 1 -SPPh 2 ){μ-κ 2 :κ 2 -SCH 2 N(Me)CH 2 -PPh 2 }] (2) resulting from S-S and P-C bond cleavage concomitant with P-S and C-S bond formation. Experiments at low temperature allowed the isolation of an intermediate species, [Fe 2 (CO) 5 -(μ-κ 1 :κ 1 -SPPh 2 ){μ-κ 2 :κ 1 -SCH 2 N(Me)CH 2 PPh 2 }] (3), differing from 2 by the coordination mode of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The formation of this product could arise from partial decomposition of dithiolate diiron compounds. 11 Unfortunately, until now, only very small single crystals of 2 were obtained. For this reason, 2 could not be identified without any ambiguity.…”
mentioning
confidence: 99%
“…The formation of this product could arise from partial decomposition of dithiolate diiron compounds. 11 Unfortunately, until now, only very small single crystals of 2 were obtained. For this reason, 2 could not be identified without any ambiguity.…”
mentioning
confidence: 99%
“…Compared to Fe 2 (SR) 2 (CO) 6 -type complexes, diiron complexes of μ-R 2 PS ligands feature elongated Fe−Fe distances by as much as 0.2 A. 32,33 Very relevant to the conversion 1 + dppv → 7 is the work of Schollhammer et al, who efficiently generated Ph 2 PS-bridged diiron complexes in good yields from the reaction of 1 and MeN(CH 2 PPh 2 ) 2 (eq 3). 32 ■ SUMMARY Theory provides guidance for the stabilization of low-spin diferrous disulfides.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…32,33 Very relevant to the conversion 1 + dppv → 7 is the work of Schollhammer et al, who efficiently generated Ph 2 PS-bridged diiron complexes in good yields from the reaction of 1 and MeN(CH 2 PPh 2 ) 2 (eq 3). 32 ■ SUMMARY Theory provides guidance for the stabilization of low-spin diferrous disulfides. The concept is simple even if the experimental verification is not; relative to Fe(I)S(−I), Fe(II)(S−II) is stabilized by the increased basicity of the ligands on iron.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mimicking the natural systems, particular attention has been paid to the preparation of mimics possessing a basic group either directly coordinating to the diiron center or locating in the secondary coordination sphere because it is believed that such a group may play a role in proton transfer in the process of proton reduction and hence improve catalytic efficiency. Wherever the base groups are located in the mimics, studies demonstrated that those groups were actively involved in the protonation of the mimics . An important consideration is that the base group in a model complex may initiate a proton‐coupled electron transfer process in catalysis.…”
Section: Introductionmentioning
confidence: 99%